Tuning ourselves into place:Enhancing multivocality with video - Bursta, Beate; Kvidal-Rovik, Trine; Rantala, Outi (Qualitative Research, 2023)
This article addresses the methodological aspects of a multi-voiced, collaborative ethnographic research process, in particular how video can enhance and amplify this research endeavour. The authors illustrate and discuss how experimental filmic methodologies can help to capture processes of becoming in a collaborative research endeavour, both enabling the development and production of diverse empirical materials and enhancing the multivocality of research practices. Using explorations of the National Tourist Route towards Havøysund in northern Norway as our empirical context, we reflect on diverse engagements along the process, such as becoming aware how the camcorder becomes a member in the research team. The filmed material forms an entanglement where our explorations along the route, our cultural practices related to the northern landscape and diverse disciplinary practices come together. We address three main ways video contributed to our research process and the creation of research materials. First, we highlight how video enables the creation of empirical traces that can be used as research materials. Second, we explore how video can work for mobilisation of multivocal dialogues. Finally, we point out that video opens the way for integration of the sensual into the research process. This article addresses the methodological aspects of a multi-voiced, collaborative ethnographic research process, in particular how video can enhance and amplify this research endeavour. The authors illustrate and discuss how experimental filmic methodologies can help to capture processes of becoming in a collaborative research endeavour, both enabling the development and production of diverse empirical materials and enhancing the multivocality of research practices. Using explorations of the National Tourist Route towards Havøysund in northern Norway as our empirical context, we reflect on diverse engagements along the process, such as becoming aware how the camcorder becomes a member in the research team. The filmed ...